Smoking cessation interventions for people living in rural and remote areas: a systematic review protocol. Issue 11 (18th November 2020) - Lum, Alistair; Skelton, Eliza; McCarter, Kristen Louise; Handley, Tonelle; Judd, Lucy; Bonevski, Billie
Abstract : Introduction: Smoking rates among people living in rural and remote areas are higher and quit rates are lower over the past 10 years compared with people living in suburban and urban areas. Higher smoking rates contribute to greater tobacco-related disease and morbidity in rural and remote areas. Physical and social isolation, greater exposure to pro-tobacco marketing, pro-tobacco social norms, and lower socioeconomic and educational levels are contributing to these higher smoking rates and lower quit rates. Smoking cessation interventions for people in rural and remote areas have been conducted, however little is known about their effectiveness or their mechanisms of action as well as the quality of such research. Behaviour change techniques (BCTs) are mechanisms of action derived from behaviour change theory, such as goal setting and reward. Improved understanding of the contribution of BCTs for smoking cessation in the rural and remote population will support future intervention development. We aim to review the literature on smoking cessation interventions for people living in rural and remote areas to inform evidence about intervention effectiveness and mechanisms of action. Methods and analysis: We will conduct a systematic review using seven scientific databases (EMBASE, MedLine, PsycINFO, CINAHL, Cochrane, Informit Health and Scopus). We will include peer-reviewed journal articles published in English that examine a smoking cessation intervention delivered to people living in rural and remote areas in the USA, Canada and Australia. We will examine outcome data relating to intervention effectiveness (eg, point prevalence abstinence or continuous abstinence), as well as the BCTs used in included interventions and their relationship with intervention outcomes. We will also assess the feasibility, acceptability and quality of research interventions of included articles, and provide graded recommendations based on the review outcomes. Data will be synthesised using narrative approaches and interpreted using content analysis. Ethics and dissemination: Ethics was not required for this systematic review. The results will be disseminated through peer-reviewed publication and at conferences by presentations. PROSPERO registration number: 177398.